Coping Styles: A Better Understanding of Stress and Anxiety in Individuals With Autism Spectrum Conditions Through Sport and Exercise Models - Irina Roncaglia (Psychological Thought, 2014)
The aim of this paper is to present an understanding of the coping mechanisms and coping styles adopted by individuals on the Autism Spectrum Conditions (ASC) by looking to draw parallels with sports performance psychology and how different sources of stress and anxiety can lead to the adoption of different coping styles. Firstly, an overview of current understanding of what constitute a stressor and how this can affect an individual is presented from sport and exercise psychology literature. Secondly, a model of coping styles is illustrated with the aim to shed light at how different perceptions of levels of stress and anxiety are managed both on an individual and group level. Thirdly, within the context of this understanding, some examples about how to support individuals on the ASC will be illustrated. Finally, implications for future research and reflection will be presented by highlighting the importance of teaching and learning coping and tolerance skills as part of a comprehensive and holistic psycho-educational program.